2011
DOI: 10.1080/08941920.2011.559654
|View full text |Cite
|
Sign up to set email alerts
|

Hunters as Stewards of Wolves in Wisconsin and the Northern Rocky Mountains, USA

Abstract: Regulated hunting may help conserve wildlife. Advocates argue hunters will champion conservation and generate revenue for management, regulation will promote sustained, stable wildlife populations, and conflicts with game species will diminish. Applying this notion to predators such as the wolf presents difficulties because of widespread human intolerance for the species. We assessed potential hunter stewardship of wolves by measuring attitudes of hunters and nonhunters in three surveys spanning 2001-2007 amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 24 publications
0
40
1
1
Order By: Relevance
“…Interest in understanding how people formulate judgments concerning acceptability of wildlife populations has given rise to parallel lines of research on human "tolerance" for and "acceptance" of wildlife (Bruskotter & Fulton, 2012;Decker & Purdy, 1988;Treves, 2009;Treves & Martin, 2011). The concept of "tolerance" for a species or population has been explored in several studies focused on people's attitudes toward carnivore populations and preferences regarding carnivore management (Naughton- Treves, Grossberg, & Treves, 2003;Treves, 2009;Treves & Martin, 2011).…”
Section: Existing Lines Of Researchmentioning
confidence: 97%
“…Interest in understanding how people formulate judgments concerning acceptability of wildlife populations has given rise to parallel lines of research on human "tolerance" for and "acceptance" of wildlife (Bruskotter & Fulton, 2012;Decker & Purdy, 1988;Treves, 2009;Treves & Martin, 2011). The concept of "tolerance" for a species or population has been explored in several studies focused on people's attitudes toward carnivore populations and preferences regarding carnivore management (Naughton- Treves, Grossberg, & Treves, 2003;Treves, 2009;Treves & Martin, 2011).…”
Section: Existing Lines Of Researchmentioning
confidence: 97%
“…However, hunters need to be actively involved in management plans, landowners need to receive associated benefits, and incomes need to exceed any financial losses associated with the presence of predators for positive effects to occur (Treves & Martin 2011). In our simulations, the demographic impacts of retaliatory killing and trophy harvest were also completely additive.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, farmers and hunters felt they were excluded from participation and involvement in carnivore management by central authorities (Ericsson & Heberlein 2003;Skogen 2003). In other parts of the world, Lindsey et al (2006) showed how local participation by trophy hunters in Africa contributed to wildlife conservation, while hunters in Wisconsin did not support wolf conservation in their area (Treves & Martin 2011;Bruskotter & Fulton 2012). In Scandinavia, hunters generally do not support the conservation of large carnivores (Ericsson & Heberlein 2003;Roskaft et al 2007).…”
Section: Introductionmentioning
confidence: 99%